Tren Perikahan di Bulan Pantangan di Sidoarjo - Riza`, Kemal; Rahmawati, Eka; Rama, Faby Toriqir; Al-Maliki, Muhammad Alwi (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2018)
Javanese people believe that there are several months that are not well chosen as the wedding month, because there are calamities or disasters that will occur in the household, namely: Suro (Muharam), Mulud (Rabiul Awal), Poso (Ramadan), and Selo (Zulkaidah). This article further examines the attitude of urban communities who have received much internalization of understanding, cultural influences, and environmental conditions that are generally industrialists against the adat ban. There are three Religious Affairs Offices (KUA) in the Sidoarjo area that are used as research objects, namely (Waru, Sedati, and Buduran). ) The reason for choosing these three locations is the typography of the area that is mostly inhabited by traditionalist Muslim communities. But in the last decade, this region has changed, from an agricultural area that relies on agriculture and fish farming, to become an industrial area with the establishment of various types of factories and other types of businesses. Based on qualitative and quantitative data, there has been a trend of behavior change in the Sidoarjo community which in the period 1984-1985 the percentage of marriages on the month was avoided a little, it was seen that there was an additional percentage according to the data taken in the last 10 years. The people of Sidoarjo are now starting to move to not be fixated on the rules of the month election. In the past, the number of couples married at four months was avoided only slightly. And now, there is a change in tendency even though the percentage is not too significant. [Orang Jawa meyakini adanya beberapa bulan yang tidak baik dipilih sebagai bulan pernikahan, karena ada bala’ atau bencana yang akan terjadi di dalam rumah tangga, yaitu: Suro (Muharam), Mulud (Rabiul Awal), Poso (Ramadan), dan Selo (Zulkaidah). Artikel ini mengkaji lebih jauh sikap masyarakat perkotaan yang sudah banyak menerima internalisasi paham, pengaruh budaya, dan kondisi lingkungan yang umumnya industrialis terhadap larangan adat tersebut. Terdapat tiga Kantor Urusan Agama (KUA) di wilayah Sidoarjo yang digunakan sebagai objek penelitian, yakni (Waru, Sedati, dan Buduran). Alasan dipilihnya tiga lokasi ini adalah tipografi kawasan yang mayoritas dihuni oleh komunitas muslim tradisionalis. Tetapi dalam dekade terakhir, kawasan ini berubah, dari kawasan agraris yang mengandalkan pertanian dan budidaya ikan, menjadi kawasan industri dengan berdirinya berbagai jenis pabrik dan jenis usaha lainnya. Berdasarkan data kualitatif dan kuantitatif, telah terjadi tren perubahan perilaku masyarakat Sidoarjo yang pada periode 1984-1985 persentase perkawinan di bulan yang dihindari sedikit, terlihat ada penambahan persentase menurut data yang di ambil pada kurun waktu 10 tahun terakhir. Masyarakat Sidoarjo saat ini mulai tergerak untuk tidak terpaku kepada aturan pemilihan bulan. Dahulu, jumlah pasangan yang menikah di empat bulan yang dihindari hanya sedikit. Dan saat ini, terdapat perubahan tendensi walau persentasenya tidak terlalu signifikan.]